Land and Citizenship in the Greek Polis: Real Property, Public Control, and Institutionalisation (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2024)
The aim of this article is to show how an approach focusing on the dynamics of the relationship between land and politeia – an aspect not often adequately considered in recent studies on the conceptualisation of citizenship as “sharing (metechein) in the polis” – can offer new elements for the analysis of institutionalisation within the Greek city. After pointing out that in Homeric society land ownership is much less exclusive than in the polis of the classical age, the first part of the essay examines, through a substantial number of epigraphic documents, aspects such as arbitration concerning the boundaries of the polis, land distributions, confiscations and expropriations of real properties, the protection of boundaries, as well as various forms of legal limitation of property rights, that all together reflect, since the sixth century BCE, the intervention of public institutions in regulating property relations within the territory of the Greek city. As a parallel and complementary phenomenon, the second part of the article looks into the various forms of property registers and records and, in particular, concentrates on the need for archival lists of citizens and properties as a prerequisite for the institutional functioning of the polis.
Keywords: citizenship; polis; land; enktesis; institutions; property; legislation